G345(P) Changes in respiratory diagnoses in pre-schoolers – a 10 year observational study. (27th April 2016) - Greenfield, G; Poots, A; Hiles, S; Blair, M
Abstract : Aims: To establish trends in diagnoses in pre-school children admitted to a large urban hospital over a 10 year period with respiratory symptoms. To explore the feasibility of developing a baseline for time trend analysis with the objective of assessing the effects of service innovations designed to improve quality of care for children with asthma and allergy. Methods: We analysed routine data in-patient attendances to the hospital between 2004 and 2013. We included all children under 5 years old where there was coding of diagnosis on discharge. Descriptive analysis of the top 5 diagnoses over 10 years. Results: There were 12, 601 admissions of children under 5 years old in the study period which accounted for 60.5% of the total admissions of children under 15 years old. Acute upper respiratory infection, acute bronchiolitis, and asthma were consistently the top 3 diagnoses in 9 out of the 10 years in this age group; over half of the diagnoses (mean 51.2%, sd 7.9, [40.3–63.3%]). Acute upper respiratory infection was the leading diagnosis in 8 out of the 10 years and ranged from 41.6% (2004) to 13.1% (2013). There was a relative reduction in the proportion of children diagnosed with URTis over this time with an increase in other categories (Figure 1 ). The majority of admissions were less than 1.6 days. Conclusion: Acute respiratory infection has been consistently the main primary diagnosis of pre-school children admitted on to our wards. The increase in "asthma" might suggest possible systematic diagnostic coding differences during this time period or a true increase in prevalence in this age group as has been described 1 . Accurate baseline data is essential especially for this age group where a diagnosis of asthma may vary considerably between practitioners and over time. Adherence to recent guidelines on accurate diagnosis in preschoolers 2 and appropriate staff training of clinicians and clinical coders may help to refine this further. References: Radhakrishnan D, Dell S, Guttmann A, Shariff S, Liu K, To T. Trends in the age of diagnosis of childhood asthma. J Allergy Clin Immunol 2014; 134(5):1057–62.e5 Saglani S, Bush A. Asthma in preschool children: the next challenge. Curr Opin Allergy Clin Immunol 2009; 9:141–5